The Use Of Smart Method In Supporting Contract Employee Selection Decisions To Become Permanent Employees At PT. Agro Muko Bunga Tanjung Estate - Jutriansyah, Dodon; Yupianti, Yupianti; Elfianty, Lena (Fakultas Ilmu Komputer Universitas Dehasen Bengkulu, 2025)
Pt. Agro Muko Bunga Tanjung Estate is a private company engaged in oil palm plantations. PT. Agro Muko Bunga Tanjung Estate has contract employees who are selected every year to become permanent employees. The process of selecting contract employees to become permanent employees is still not effective and efficient, this will result in doubt in decision making which allows for errors to occur and is less precise. The SMART method is a multi-criteria decision-making technique that is effective in dealing with problems at PT. Agro Muko Bunga Tanjung Estate. The use of the SMART method in the selection of contract employees to become permanent employees at PT. Agro Muko Bunga Tanjung Estate can simplify the selection process based on 4 assessment criteria, namely Length of Work Contract, Education, Attendance, and Responsibilitylity. The final result of this research is a decision support system for the selection of contract employees to become permanent employees that is in accordance with expectations and the system or application can provide information on the results of the selection of contract employees through the rank after the year of research.